Type 1 insulin-like growth factor signalling in malignant melanoma - Goodfellow, M; Mark Robert Goodfellow (2012)
Novel therapeutic strategies are sorely required for malignant melanoma, which has been shown to overexpress the type 1 insulin-like growth factor receptor (IGF1R) compared to benign naevi. The IGF1R mediates many features of the malignant phenotype and is an attractive anti-cancer therapeutic target. Inoculation with IGF1R depleted tumour cells has been shown to upregulate MHC Class 1 expression and confer protection from tumour rechallenge in vivo. The initial aim of this project was to investigate effects of IGF1R depletion on MHC Class 1 expression and its functional significance in melanoma cells. IGF1R gene silencing, but not IGF1R inhibition, caused a significant increase in surface MHC Class 1 expression in one murine cell line, B16.F10, but 0/8 human melanoma cell lines. In B16.F10 cells, increased MHC Class 1 did not affect cell lysis or cytokine production by, or proliferation of, activated T lymphocytes in vitro. These results indicate that the increase in MHC Class 1 in melanoma cells is not of functional significance. The main focus of this project then addressed a key issue relevant to clinical trials of IGF1R inhibition. Identifying features which render melanoma cells sensitive to IGF1R inhibitors is important to select patients suitable to receive this therapy. The approach was to define changes in gene expression after IGF1 or IGF1R inhibitor treatment of melanoma cells. Initial experiments were performed to select concentrations of IGF1 and IGF1R inhibitor AZ12253801, the latter based on GI50 concentrations. An IGF gene signature was created which was significantly correlated to Ki67 expression, a proliferation marker, in clinical datasets. This suggests a rationale for IGF1R targeting in clinical melanoma. Gene expression profiling identified that IGF and IGF1R inhibition had reciprocal effects on expression of HBP1, a transcriptional repressor of prognostic significance in breast cancer. HBP1 was validated as an IGF1 regulated gene, and experiments using signalling inhibitors indicated that IGF1R regulates HBP1 via the PI3K pathway. HBP1 depletion did not influence effects of IGF1R inhibition on proliferation. However HBP1 induction appeared to mediate effects of AZ12253801 on inhibiting the WNT pathway, measured by TOP/FOP reporters, and HBP1 depletion enhanced basal and WNT-induced NMYC expression. NMYC has not previously been reported to be a Wnt/β catenin target gene in neoplastic cells. These results encourage further investigation into the effects of IGF1R in regulating HBP1, particularly with respect to dual IGF1R Wnt/β catenin targeting.